Vaktelproduktion för ägg och kött - Andersson, Lisa (SLU/Dept. of Animal Nutrition and Management (until 231231), 2010)
The aim of this study is to review the commercial quail production for eggs and meat in the world. Another aim is to review the potential for increased production. Globally the quail production is very small, except in China where it is the second largest poultry industry. The production globally is small despite the quail's rapid growth, early sexual maturity and its high feed efficiency. The quail is also used as a laboratory animal and can be reared to be released in hunting areas. Egg laying quails from good lines has a yearly production of 300-320 eggs and quails for meat production is slaughtered after 4-6 weeks at a weight of 180-200 grams. There is no difference between eggs and meat from quails and eggs and meat from laying hens and broiler chickens from a nutritional standpoint. However, the quail requires a small space, low investments and reaches both sexual maturity and slaughter weight quickly. Some scientists also claim that the quail is more resistant to disease and a more efficient feed converter of feed to eggs than the laying hen. All of these qualities are very beneficial and especially in poor communities where quail has a potential of becoming an important food source. The popularity has however, differed between countries. If the quail production is to grow, more research is needed. The breeding is generally very concentrated on production qualities and very little research has been made on for example genotype-environmental interaction. Some reports claim that the quail now is suffering from lowered fertility rates and a lower resistance to disease believed to be caused by an inbreeding depression. This problem has to be solved in order for the quail production to be a more important alternative to other poultry industries.